Intravitreal application of AAV-BDNF or mutant AAV-CRMP2 protects retinal ganglion cells and stabilizes axons and myelin after partial optic nerve injury - Chiha, Wissam; Bartlett, C.A.; Petratos, S.; Fitzgerald, Melinda; Harvey, A.R. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
© 2020 Elsevier Inc. Secondary degeneration following an initial injury to the central nervous system (CNS) results in increased tissue loss and is associated with increasing functional impairment. Unilateral partial dorsal transection of the adult rat optic nerve (ON) has proved to be a useful experimental model in which to study factors that contribute to secondary degenerative events. Using this injury model, we here quantified the protective effects of intravitreally administered bi-cistronic adeno-associated viral (AAV2) vectors encoding either brain derived neurotrophic factor (BDNF) or a mutant, phospho-resistant, version of collapsin response mediator protein 2 (CRMP2T555A) on retinal ganglion cells (RGCs), their axons, and associated myelin. To test for potential synergistic interactions, some animals received combined injections of both vectors. Three months post-injury, all treatments maintained RGC numbers in central retina, but only AAV2-BDNF significantly protected ventrally located RGCs exclusively vulnerable to secondary degeneration. Behaviourally, treatments that involved AAV2-BDNF significantly restored the number of smooth-pursuit phases of optokinetic nystagmus. While all therapeutic regimens preserved axonal density and proportions of typical complexes, including heminodes and single nodes, BDNF treatments were generally more effective in maintaining the length of the node of Ranvier in myelin surrounding ventral ON axons after injury. Both AAV2-BDNF and AAV2-CRMP2T555A prevented injury-induced changes in G-ratio and overall myelin thickness, but only AAV2-BDNF administration protected against large-scale myelin decompaction in ventral ON. In summary, in a model of secondary CNS degeneration, both BDNF and CRMP2T555A vectors were neuroprotective, however different efficacies were observed for these overexpressed proteins in the retina and ON, suggesting disparate cellular and molecular targets driving responses for neural repair. The potential use of these vectors to treat other CNS injuries and pathologies is discussed.